2012
DOI: 10.1029/2011jc007112
|View full text |Cite
|
Sign up to set email alerts
|

What controls primary production in the Arctic Ocean? Results from an intercomparison of five general circulation models with biogeochemistry

Abstract: [1] As a part of Arctic Ocean Intercomparison Project, results from five coupled physical and biological ocean models were compared for the Arctic domain, defined here as north of 66.6°N. The global and regional (Arctic Ocean (AO)-only) models included in the intercomparison show similar features in terms of the distribution of present-day water column-integrated primary production and are broadly in agreement with in situ and satellite-derived data. However, the physical factors controlling this distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(161 citation statements)
references
References 107 publications
5
156
0
Order By: Relevance
“…This observation is not necessarily new [Popova et al, 2012;Vancoppenolle et al, 2013], but one should be cautious when interpreting this result because these three simulated parameters were positively biased (i.e., means usually overestimated) (Figures 8 and 9). For example, the simulated, mean surface NO 3 was vastly overestimated, especially in the lowproductivity, nutrient-depleted interior regions of the Arctic Ocean, i.e., the Beaufort Sea and the central Arctic Basin where model and in situ iNPP agreed best (Figures 6b and 6e; Table 4).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This observation is not necessarily new [Popova et al, 2012;Vancoppenolle et al, 2013], but one should be cautious when interpreting this result because these three simulated parameters were positively biased (i.e., means usually overestimated) (Figures 8 and 9). For example, the simulated, mean surface NO 3 was vastly overestimated, especially in the lowproductivity, nutrient-depleted interior regions of the Arctic Ocean, i.e., the Beaufort Sea and the central Arctic Basin where model and in situ iNPP agreed best (Figures 6b and 6e; Table 4).…”
Section: Discussionmentioning
confidence: 89%
“…Earlier intercomparison studies for the Arctic Ocean emphasized the importance of a realistic representation of ocean physics [Popova et al 2012], in particular vertical mixing and nutrient concentration, for accurate Arctic Ocean ecosystem modeling. Five BOGCMs manifested similar levels of light limitation owing to a general agreement on the simulated sea ice distribution [Popova et al 2012]. On the other hand, the ESMs participating in the Vancoppenolle et al [2013] study showed that Arctic phytoplankton growth was more limited by light related to sea ice than by nutrient availability for the period of 1980-1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seawater nutrient concentrations feature strong regional variations, but in the Arctic, those are not well constrained: the World Ocean Atlas Climatology [Garcia et al, 2006] has almost no data coverage in the Arctic Basin, and riverine inputs of nutrients are poorly understood [Popova et al, 2012]. Some general features can however be found in the literature.…”
Section: Macro-nutrients In Sea Ice and In The Water Columnmentioning
confidence: 99%
“…The ice algae model of Jin et al [2006] has been included into a large-scale ocean modelling system running at regional scales [Deal et al, 2011;Jin et al, 2012], while an N-P-Z 3D ice-ocean model has been applied to the Hudson Bay [Sibert et al, 2011]. These studies indicate a moderate role for ice algae in the Arctic carbon cycle, reaching 15% of the total Arctic production [Deal et al, 2011].…”
Section: Modelling and Up-scaling The Role Of Sea Ice In The Marine Bmentioning
confidence: 99%